2021
DOI: 10.1093/nar/gkab431
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte meiosis-coupled poly(A) polymerase α phosphorylation and activation trigger maternal mRNA translation in mice

Abstract: Mammalian oocyte maturation is driven by strictly regulated polyadenylation and translational activation of maternal mRNA stored in the cytoplasm. However, the poly(A) polymerase (PAP) that directly mediates cytoplasmic polyadenylation in mammalian oocytes has not been determined. In this study, we identified PAPα as the elusive enzyme that catalyzes cytoplasmic mRNA polyadenylation implicated in mouse oocyte maturation. PAPα was mainly localized in the germinal vesicle (GV) of fully grown oocytes but was dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…HPG signals were detected using a Click-iT®HPG Alexa Fluor®Protein Synthesis Assay Kit (Life Technologies). Mean intensity of the HPG signal was measured across the middle of each oocyte and quantified using ImageJ software 53 .…”
Section: Methodsmentioning
confidence: 99%
“…HPG signals were detected using a Click-iT®HPG Alexa Fluor®Protein Synthesis Assay Kit (Life Technologies). Mean intensity of the HPG signal was measured across the middle of each oocyte and quantified using ImageJ software 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated that ERK1/2 regulates the maternal mRNA translation and decay in mouse oocytes from the GV to MII stage (Sha et al , 2017 ; Jiang et al , 2021 ), and defects in maternal mRNA degradation is associate with early embryonic arrest (Sha et al , 2020a , 2020b ). However, whether MOS is required for maternal mRNA decay in human oocytes is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…PAPγ exhibits monoadenylation activity toward small RNAs and is active during tumorigenesis (Topalian et al, 2001). Very recently, Jiang et al (2021) identified PAPα as the elusive enzyme that catalyses cytoplasmic polyadenylation of maternal mRNAs in mouse oocytes (Table 2). Inhibition of PAPα activity through overexpression of a PAPα mutant impaired cytoplasmic polyadenylation and translation of maternal mRNAs, thus preventing meiotic progression.…”
Section: Translational Regulation Of Maternal Mrnasmentioning
confidence: 99%